2012
DOI: 10.3892/ijmm.2012.1223
|View full text |Cite
|
Sign up to set email alerts
|

A novel dual oxidase maturation factor 2 gene mutation for congenital hypothyroidism

Abstract: Congenital hypothyroidism (CH) is caused by thyroid hormone deficiency present at birth. DUOXA2 (dual oxidase maturation factor 2) is one of the prerequisites for thyroid hormone synthesis. The present study explored the novel mutations of DUOXA2 in CH patients. Genomic DNA was extracted from peripheral blood of 47 unrelated CH patients, their family members and 100 healthy controls. All 6 exons and their flanking sequences of the DUOXA2 gene were PCR amplified and sequenced. Sequencing results were compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
(8 reference statements)
1
18
0
Order By: Relevance
“…Next-generation sequencing-based comprehensive mutation screening showed that the patient was compound heterozygous for 2 previously reported nonsense DUOXA2 mutations (p.[Tyr138*] [15] and p.[Tyr246*] [7]). The parents harbored 1 mutation each in a heterozygous state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next-generation sequencing-based comprehensive mutation screening showed that the patient was compound heterozygous for 2 previously reported nonsense DUOXA2 mutations (p.[Tyr138*] [15] and p.[Tyr246*] [7]). The parents harbored 1 mutation each in a heterozygous state (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, DUOX1 (and possibly DUOXA1) could have a minor role in H 2 O 2 production in the thyroid, because CH in biallelic DUOX2 mutation carriers is often transient [6], and those mutation carriers produce thyroid hormones presumably via DUOX1 in the post-infantile period [7]. As for DUOXA2 mutation carriers, only four unrelated CH patients have been reported [5,[8][9][10], and thus the phenotypic spectrum remains to be established. Here, we report the fifth DUOXA2 mutation-carrying CH patients, whose brother also had the identical homozygous mutation but did not have CH.…”
Section: Functional Analysesmentioning
confidence: 99%
“…Next generation sequencing-based comprehensive genetic analysis of the proband led us to identify a homozygous nonsense DUOXA2 mutation (c.413dupA, p.Tyr138*) that had been previously described [9]. No mutation was found in the other sequenced genes.…”
Section: Mutation Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…15%-20% of CH patients with thyroid dyshormonogenesis combined with thyroid goiter [1] is inherited as an autosomal recessive trait [10] . Genetic defects of enzymes in the thyroid hormone synthesis pathway, such as DEHAL1 [11] , thyroglobulin (TG) [12] , thyroid peroxidase (TPO) [13] , dual oxidase 2 maturation factor (DUOXA2) [14] , dual oxidase 2 (DUOX2) [15] , sodium-iodide symporter (NIS) [16] and Pendred syndrom (PDS) [17] , can cause thyroid dyshormonogenesis.…”
Section: Introductionmentioning
confidence: 99%